Lingkungan Fisik Rumah dan Kejadian Tuberkulosis paru di Indonesia - Alchamdani Alchamdani; Nadila Puspita Ningsi (FORIKES, 2022)
The environment is one of the risk factors that influence the incidence of pulmonary tuberculosis in Indonesia. The purpose of this article is to determine the relationship between the risk factors of the physical home environment and the incidence of pulmonary tuberculosis in Indonesia. The method used in writing this article is a literature review. This study uses the Google Scholar search engine. The period of the article is from 2014 to 2020 with the keywords